Agent-based model of the Russian banking system: Calibration for maturity, interest rate spread, credit risk, and capital regulation. Issue 1 (3rd April 2021) - Ermolova, Maria; Leonidov, Andrey; Nechitailo, Vladimir; Penikas, Henry; Pilnik, Nikolay; Serebryannikova, Ekaterina
ABSTRACT: The Basel III regulation raised the minimum capital requirements for banks. However, its implementation may not have reduced systemic risks. Academicians investigating optimal banking regulations do not have a consensus on whether to increase or decrease capital requirements. Here, we use the agent-based approach to study capital regulation and its implications on the evolution of the banking system. We chose the Russian banking system to proxy key model parameters. We find that lower capital requirements imply higher financial stability than the Basel III regime, where the regulator requires banks to have capital over 10% of its risk-weighted assets' amount. However, the regulatory rule to merely have a non-negative capital is the simplest solution that best fits heterogeneous economies. It produces the highest ratio of capital to assets, the least number of bank bankruptcies, and the lowest demand of banks to enter the interbank market to cover liquidity problems for all systems.